THE IMPORTANCE OF CLARITY IN BALANCE SHEET DISPLAY. - Payne, Robert E. (The Accounting Review, 1933)
Abstract The article focuses on importance of clarity in balance sheet display. One of the most important pieces of work which a public accountant is called upon to perform is the preparation and analysis of balance sheets and financial conditions. By no means is this the mere listing of certain assets and liabilities. It resolves itself into a matter of judgment in arrangement and valuation, and judgment is often a matter of one's experience in judging and noting the results in previous situations. The matter of prime importance to consider is the type of person who will be called upon to read the balance sheet. In a recent examination, it was discovered that the management had been giving itself some systematize, but serious-minded kidding by working on the assumption that installment accounts receivable were not subject to the need forbad debt reserves. This is a matter of problem of valuation. According to the author, balance sheets must be prepared for the benefit of the reader and must be grouped to give him the benefit of the most accurate information available, in the most readable form. It should give him all of the facts and the facts should be stated clearly.